Narratives of self-help of cyberporn dependents. - Cavaglion G (Sexual Addiction & Compulsivity, 2008)
This paper focuses on 2,000 messages sent by 302 participants in an Italian self-help Internet community for cyberporn dependents (noallapornodipendenza) founded in 2003. Through anonymous surfing, participants form a support community which takes them on a safe journey of self-expression and emotional involvement based on the principle of 'like cures like.' This study uses a qualitative text analysis to depict the key narratives of these cyberporn users and isolate major patterns of sharing, coping, and recovery. Similarities with encounter group strategies for other types of addiction are discussed.